Digital Technology as a Communication Media in Improving Students' Knowledge - Diah Nirmala Dewi; Komang, Trisna Dewi (Prodi Pendidikan Bahasa Inggris, Universitas PGRI Banyuwangi, 2025)
This study aimed to understand how digital technology, as a communication tool, can help improve students' knowledge. The researcher used a descriptive qualitative approach. To gather information, the study included library research and interviews. The data came from students' opinions about digital technology. There were 5 students being interviewed. The data was processed in four steps: collecting the data, organizing it, analyzing it, and describing it. From the results, the researcher found that when digital technology improves, it gives students many ways to get the knowledge they need.